Dynamics of the PI3K-like protein kinase members ATM and DNA-PKcs at DNA double strand breaks - Davis, Anthony J (Landes Bioscience, 2010)
The protein kinases ATM and DNA-PKcs play critical roles in the cellular response to DNA double strand breaks (DSBs). ATM and DNA-PKcs are activated in response to DSBs and play several important roles in propagation of the damage signal and for the repair of DNA damage. Recent work from several groups, including ours, has focused on studying the dynamics of each of these proteins at DSBs and the requirements and factors which play a role(s) in this process. The use of live cell imaging of fluorescently-tagged ATM and DNA-PKcs has allowed us to study the real-time response of these proteins to laser-generated DNA damage in vivo. Here, we will extensively discuss the behavior of the ATM and DNA-PKcs proteins at DSB sites.